2017
DOI: 10.1017/s104161021700134x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and correlates of traumatic brain injury (TBI) in older adults: results from the Well-being of the Singapore Elderly (WiSE) study

Abstract: The current study provides information on the prevalence and associated factors of TBI in the older adult population in Singapore. Since TBI was associated with older adults with diabetes, they must be cautioned about fall risk. Also, given the association with disability, older adults with TBI are likely to require support and rehabilitative care to ensure good quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…Overall, taking into account the impact of age on disability, our estimates of disability are consistent both with prior NHANES publications using the same disability definitions 20,21 and with other studies using data representative of the US population. 31,32 What is consistent across all studies on head injury and disability is that head injury is associated with a significant burden of disability, 8-11,13-16 and the results of our study provide nationally representative estimates for the entire US population.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Overall, taking into account the impact of age on disability, our estimates of disability are consistent both with prior NHANES publications using the same disability definitions 20,21 and with other studies using data representative of the US population. 31,32 What is consistent across all studies on head injury and disability is that head injury is associated with a significant burden of disability, 8-11,13-16 and the results of our study provide nationally representative estimates for the entire US population.…”
Section: Discussionsupporting
confidence: 78%
“…[13][14][15][16] A population-based cohort study in Sweden (participants 18-64 years of age) defining head injury (with or without loss of consciousness) from hospital registers reported that ≈44% of individuals with a history of head injury had at least 1 disability 3 years after injury, 16 and other studies from France 15 (median age 50 years), Ontario, Canada (participants ≥18 years of age), 14 and Singapore 13 (participants ≥60 years of age) also reported increased disability among individuals with a history of head injury (head injury defined by self-report of injury-related harm or permanent sequelae due to a traumatic brain injury 15 and by self-reported questions about head injury with loss of consciousness 13,14 ) compared to those without a history of head injury. Similar to our study, the majority of prior studies that used a self-reported head injury definition did not have the information to report time between head injury and disability ascertainment, 9,[12][13][14] while studies using hospitalization records typically did report time between head injury and disability ascertainment. 8,10,16 Our results extend the existing literature by providing nationally representative prevalence estimates from the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TBI remains a significant clinical challenge in spite of several breakthroughs of trauma management strategies in recent years [25]. The incidence of TBI is up to 2-3% in the industrialized countries in Europe, and it has been ranked as one of the leading causes of morbidity and mortality of adolescent and adults under 40 years of age all over the world [26]. The lasting and long-term syndrome composing of brain edema, cerebral infraction, intracranial hypertension, neural inflammation, necrosis, hydrocephalus, BBB dysfunction and so on makes TBI management more challenging and complex compared to the primary structure destruction caused by TBI itself [27].…”
Section: Discussionmentioning
confidence: 99%